ANALISIS PENGUKURAN KINERJA PEMERINTAH DAERAH DENGAN MENGGUNAKAN PENDEKATAN VALUE FOR MONEY (STUDI KASUS PADA KABUPATEN NABIRE TAHUN 2019-2021) - Indah Putri Nurafifah; Haliah Haliah; Nirwana Nirwana (Jurnal Akuntansi dan Bisnis, 2022)
This study aims to determine the performance of Pemerintah Daerah Kabupaten Nabire using the Value For Money approach in 2019-2021. Value For Money is a concept of managing public sector organizations based on three main elements, namely economy, efficiency, and also effectiveness. This research is a quantitative descriptive study, where this research will describe the phenomena or characteristics of the data during the period 2019, 2020 and 2021 using the value for money method approach which consists of the analysis of Economic Ratios, Effectiveness Ratios and Efficiency Ratios. This research was conducted at Pemerintah Daerah Kabupaten Nabire using secondary data sources. Secondary data obtained in the form of documentation, namely the number of results from the APBD and RAPBD of the Pemerintah Daerah Kabupaten Nabire on the DJPK (Directorate General of Fiscal Balance) Data Portal website of the Ministry of Finance: https://djpk.kemenkeu.go.id/portal/data/apbd. This study shows that the performance of the Pemerintah Daerah Kabupaten Nabire has not met the value for money principle because the economic ratio shows a value of > 100% in 2019 and 2021 meaning it is not economical because the realization of expenditure is greater than the budget, the efficiency ratio shows a value of > 100% in 2019 meaning that it is inefficient because the realization of expenditure is greater than the realization of income, and the effectiveness ratio shows a value of <100% in 2019-2020 which means that it is not effective because the realization of income is smaller than the revenue budget.